Pengaruh Gigi Molar Tiga Atas pada Kejadian Perikoronitis Gigi Molar Tiga Bawah - Harniati, Etny Dyah; Rahayoe, Poerwati Soetji (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
The impaction of the lower third molar is an impaction that commonly happens, approximately 98% of 10.979 impacted molars found in the study on 5.000 cadets. The condition of the impaction tend to cause several pathological conditions, which one of them is pericoronitis, where this condition at once becomes one of the most reasonable reasons for extraction on the involved impacted molars to be performed. The aim of this research was to identlfv the eï¬‚ects of the upper third molar on the existence of pericoronitis of the lower third molar: Design of this research was an analytical observational study using the cross sectional approach over 6 months. This research was conducted through the direct observation and roentgen photo on 62 patients with the impaction of the lower third molar either with pericoronitis or without pericoronitis in the hospital of RSU PKU Muhammadiyah Yogyakarta. The observation was done to the patients with pericoronitis to idenhjy the correlation between the traumatic occlusion with the appearance of pericoronitis. The observation was also conducted to identijjz the correlation between the level of impaction with the traumatic occlusion and the correlation between the position of the upper third molar with the traumatic occlusion. During the research, there gained 62 sampels was gained, divided into 29 samples with pericoronitis and 33 samples without pericoronitis. The occurrence of the pericoronitis with trauma was mostly seen on the level A of impaction with the position of the upper third molar is bucoversion (90,9%), while the occurrence of pericoronitis without trauma was mostly seen on the vertical upper third molar with level B of impaction (83,3%). From the analysis test of Chi-Square, showed a significant correlation between the traumatic occlusion with the occurrence of pericoronitis (z2 0, 05) and there was an eï¬ect of the upper third molar position and the impaction level with trauma (p 0,05), while the upper third molar with pericoronitis and the impaction level with pericoronitis did not show any signiï¬cant inï¬‚uence Q2 0,05). The analysis test of Man-Whitney showed that the bucoversion upper third molar position mostly caused trauma (p 0, 05). Upper third molar; the impaction level and the trauma with recurrent pericoronitis or first pericoronitis did not show any significant inï¬‚uence (p 0, 05).